The synthesis and fluorescence properties of novel chromenone-crown ethers - SALAN, ÜMİT (TAYLOR & FRANCIS LTD, 2010)
o-Dihyroxy-3-phenylchromenone derivatives, namely, 6,7-dihydroxy-3-(3',4'-dimethoxyphenyl)chromenone and 6,7-dimethoxy-3-(3',4'-dihydroxyphenyl)chromenone, were obtained from 2,4,5-trihydroxybenzaldehyde/3,4-dimethoxyphenylacetic acid and 2-hydroxy-4,5-dimethoxybenzaldehyde/3,4-dihydroxyphenylacetic acid, respectively, in the presence of acetic anhydride and sodium acetate under an inert atmosphere, after treatment with MeOH/HCl(aq). The chromenone-crown ethers were prepared from cyclic condensation of o-dihydroxy-3-phenylchromenones with poly(ethylene glycol) ditosylates in the presence of CH3CN/alkali metal carbonates. The chromatographically purified novel chromenone-crown ethers were identified by 1H NMR, MALDI-TOF mass spectrometry and elemental analysis. The fluorescence and UV-vis spectroscopic properties of the obtained chromenone-crown ethers and their complexes with Li+, Na+ and K+ perchlorate salts were estimated in acetonitrile. The quantum yields of novel chromenone-crown ethers were determined by the comparative method. [image omitted].
Keywords: chromenone-crown ethers; 3-phenylchromenone; quantum yield; synthesis; cation binding; CATION-BINDING; COMPLEXATION; CONDUCTOMETRY; MACROCYCLES; RECOGNITION; DERIVATIVES; EXTRACTION; SPECTRA